A Converse Lyapunov Theorem and Robustness with Respect to Unbounded Perturbations for Exponential Dissipativity. (23rd May 2010) - Li, Xudong; Guo, Yuan
Abstract : This paper is concerned with the nonlinear systemx ′ ( t ) = f ( t, x ( t ) ) . We give a converse Lyapunov theorem and prove robustness of uniform exponential dissipativity with respect to unbounded external perturbations, without assumingf being globally Lipschitz inx .